2009
DOI: 10.1186/1756-8722-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Gastrointestinal Oncology – insights from the 2008 44th annual meeting of the American Society of Clinical Oncology

Abstract: We have reviewed the pivotal presentations rcelated to colorectal cancer (CRC) and other gastrointestinal malignancies from 2008 annual meeting of the American Society of Clinical Oncology (ASCO). We have discussed the scientific findings and the impact on practice guidelines and ongoing clinical trials. The report on KRAS status in patients with metastatic CRC receiving epidermal growth factor receptor (EGFR) targeted antibody treatment has led to a change in National Comprehensive Cancer Network guideline th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…[10][11] Unlike wild-type KRAS proteins, which are self-inactivated after a short time, mutant proteins are locked in a conformation that continuously activates signaling pathways in the absence of any upstream stimulation of the EGFR receptor. 4,7,8 On this basis, therapeutic guidelines suggest that anti-EGFR treatment of metastatic colorectal carcinoma is only suitable and beneficial for patients with tumors demonstrating normal (wild-type) KRAS. It has been shown that KRAS mutations are frequently associated with resistance to anti-EGFR therapy, 8,12,13 and in general, patients with KRASmutated tumors will not benefit from EGFR-targeted cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11] Unlike wild-type KRAS proteins, which are self-inactivated after a short time, mutant proteins are locked in a conformation that continuously activates signaling pathways in the absence of any upstream stimulation of the EGFR receptor. 4,7,8 On this basis, therapeutic guidelines suggest that anti-EGFR treatment of metastatic colorectal carcinoma is only suitable and beneficial for patients with tumors demonstrating normal (wild-type) KRAS. It has been shown that KRAS mutations are frequently associated with resistance to anti-EGFR therapy, 8,12,13 and in general, patients with KRASmutated tumors will not benefit from EGFR-targeted cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Various demographic and tumor characteristics were compared between the 2 groups, including "early onset" (less than 40 y) or "late onset" (40 y or older), sex, tumor site (right proximal to splenic flexure or left distal to splenic flexure), size ( < 3 or Z3 cm), gross configuration (polypoid, ulcerated, or circumferential), histologic type (usual or unusual mucinous, signet ring cell, medullary, and undifferentiated), grade (low-well and moderately differentiated or highpoorly differentiated and undifferentiated), mucinous component in tumor (present or absent), lymphovascular invasion (LVI) (present or absent), extramural venous invasion (EMVI) (present or absent), perineural invasion (PNI) (present or absent), peritumoral lymphocytic response (presence or absence), intratumoral lymphocytes (ITL) (present or absent), tumor border (pushing or infiltrative), depth of tumor invasion (T) status (intramural T1-T2 or extramural T3-T4), regional lymph node (N) status (positive or negative), distant metastasis (M) status at initial presentation (positive or negative), and overall stage (low stage 1-2 or high stage [3][4]. Various demographic and tumor characteristics were compared between the 2 groups, including "early onset" (less than 40 y) or "late onset" (40 y or older), sex, tumor site (right proximal to splenic flexure or left distal to splenic flexure), size ( < 3 or Z3 cm), gross configuration (polypoid, ulcerated, or circumferential), histologic type (usual or unusual mucinous, signet ring cell, medullary, and undifferentiated), grade (low-well and moderately differentiated or highpoorly differentiated and undifferentiated), mucinous component in tumor (present or absent), lymphovascular invasion (LVI) (present or absent), extramural venous invasion (EMVI) (present or absent), perineural invasion (PNI) (present or absent), peritumoral lymphocytic response (presence or absence), intratumoral lymphocytes (ITL) (present or absent), tumor border (pushing or infiltrative), depth of tumor invasion (T) status (intramural T1-T2 or extramural T3-T4), regional lymph node (N) status (positive or negative), distant metastasis (M) status at initial presentation (positive or negative), and overall stage (low stage 1-2 or high stage [3][4].…”
Section: Morphologic Analysismentioning
confidence: 99%
“…Chemotherapeutic agents utilized for the treatment/management of colorectal cancer include irinotecan (IT), 5-fluorouracil (5-FU) and oxaliplatin (OX) [61]. We have previously reported that these chemotherapeutic agents upregulate the cell surface expression of CD26 [62].…”
Section: Apigenin Enhances the Effect Of Chemotherapeutic Agents In Umentioning
confidence: 99%
“…Both cetuximab and panitumumab monoclonal anti-EGFR antibodies are eVective only in the treatment of mCRCs with a wild-type k-ras gene, whereas patients with tumors harboring k-ras mutations appear to be resistant [a deWnitive trial of single agent panitumumab demonstrated response in 20 or 30% (when added to chemotherapy treatment) of patients whose tumors exhibited a wild-type k-ras gene, but none in those harboring k-ras mutations] (Linardou et al 2008;Saltz 2008;Mayer 2009). Such research reports of k-ras status in mCRC patients receiving EGFR-targeted antibody treatment have led to a change in the National Comprehensive Cancer Network guidelines, which recommend that only patients with wild-type KRAS tumor should receive this treatment (Javle and Hsueh 2009). In a metaanalysis, it was found that resistance to EGFR-targeted therapy also occurs in a substantial number of patients with essentially wild-type k-ras, indicating however that additional mechanisms of resistance exist (Linardou et al 2008).…”
Section: Non-small Cell Lung Cancermentioning
confidence: 92%
“…The addition of bevacizumab to gemcitabine and erlotinib has not been found to be superior to gemcitabine and erlotinib for advanced disease (Javle and Hsueh 2009). Increased understanding of the EGFR pathway may permit the use of other targeted agents to either augment therapeutic eYcacy or circumvent resistance.…”
Section: Pancreatic Cancermentioning
confidence: 98%